The Staphylococcus aureus Network Adaptive Platform Trial Protocol: New Tools for an Old Foe. (19th June 2022) - Tong, Steven Y C; Mora, Jocelyn; Bowen, Asha C; Cheng, Matthew P; Daneman, Nick; Goodman, Anna L; Heriot, George S; Lee, Todd C; Lewis, Roger J; Lye, David C; Mahar, Robert K; Marsh, Julie; et al.
Abstract: Staphylococcus aureus bloodstream (SAB) infection is a common and severe infectious disease, with a 90-day mortality of 15%–30%. Despite this, <3000 people have been randomized into clinical trials of treatments for SAB infection. The limited evidence base partly results from clinical trials for SAB infections being difficult to complete at scale using traditional clinical trial methods. Here we provide the rationale and framework for an adaptive platform trial applied to SAB infections. We detail the design features of the Staphylococcus aureus Network Adaptive Platform (SNAP) trial that will enable multiple questions to be answered as efficiently as possible. The SNAP trial commenced enrolling patients across multiple countries in 2022 with an estimated target sample size of 7000 participants. This approach may serve as an exemplar to increase efficiency of clinical trials for other infectious disease syndromes. Abstract : The Staphylococcus aureus Network Adaptive Platform (SNAP) trial is a multicenter international adaptive platform trial that will simultaneously address multiple key questions in the management of S. aureus bloodstream infections and involve >7000 adult and child participants.